Finding the appropriate mode of dispute resolution: Introducing neutral evaluation in the Subordinate Courts - QUEK ANDERSON, Dorcas (Institutional Knowledge at Singapore Management University, 2011)
The Alternative Dispute Resolution (ADR) movement has gained significant traction over the last three decades and has been expanding at a rapid pace in many common law jurisdictions. The allure of ADR lies, in large part, in its recognition of litigants’ desire for self-determination and autonomy in resolving their disputes. ADR became even more attractive as dissatisfaction with the traditional court system grew. In the seminal Roscoe Pound Conference on Popular Causes of Dissatisfaction with the Administration of Justice in USA, the changing role of the courts was highlighted, casting ADR further into the spotlight.i Instead of offering only adjudication in a conventional trial setting, the courts were envisaged as a “multidoor courthouse” – a comprehensive justice centre in which cases are screened and referred to the most effective dispute resolution process.ii This philosophy for the administration of justice has since been embraced by many judiciaries, including Singapore. Both litigation and ADR are now crucial components of the dispute resolution framework of many jurisdictions, with each serving its own distinct functions. The role of the lawyer has accordingly been recast in light of this reality - the lawyer, faced with the convergence of the cultures of litigation and consensus-building, will now have to adopt a “more nuanced, multi-pronged strategic approach to both fighting and settling”